FUZZY LOGIC UNTUK MEMPREDIKSI PEMAKAIAN LISTRIK MENGGUNAKAN METODE MAMDANI - Suprapto, Hendra; Simanjuntak, Pastima (LPPM Universitas Putera Batam, 2020)
Electricity is a source energy need in all aspects of human activity, including in industries, urban society and rural society. Prediction is a logically forecast of the upcoming occurrence based on data and information. Fozzy logics is a method that can be used to solve this issue for it has a strong tolerance toward invalid data and uncertain data. At the present, there is no system that can predict electricity usage yet. This research was conducted to design a decision-making system on the prediction of electricity usage using Fuzzy logics and mamdani method. The data processing system and the system were developed using matlab application with three inputs; power, total KwH and time, resulting in prediction outcomes. The data analysis showed the results of each manual measurement of 50.766, 54.038 and 61.25 respectively. Meanwhile, the results of the system measurement using matlab obtained 50, 57.7 and 60.3 respectively. Therefore, it can be drawn into conclusion that the mamdani method has been able to help the society in making decision related to electricity usage prediction.